2021
DOI: 10.3389/fphar.2021.679388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pirfenidone and Nintedanib in a Human Lung Model of Fibrogenesis

Abstract: Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal lung disease with a poor prognosis and increasing incidence. Pirfenidone and nintedanib are the only approved treatments for IPF but have limited efficacy and their mechanisms of action are poorly understood. Here we have examined the effects of pirfenidone and nintedanib in a human model of lung fibrogenesis, and compared these with the putative anti-fibrotic compounds Lipoxin A4 (LXA4), and senicapoc, a KCa3.1 ion channel blocker.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…We observed an increase of α-SMA, collagen-1, and fibronectin 1 after the treatment with pirfenidone, suggesting that although evidence shows its anti-fibrotic effect in proliferative fibroblasts (COLLINS; RAGHU, 2019), the same effect is not perceived in senescent fibroblasts. In agreement with our findings, Roach et al (2021) and collaborators found an increased expression of α-SMA, deposition of collagen 1 and collagen-3, and secretion of soluble collagen after treating fibroblasts with nintedanib and pirfenidone (ROACH; CASTELLS; DIXON; MASON et al ., 2021).…”
Section: Discussionsupporting
confidence: 92%
“…We observed an increase of α-SMA, collagen-1, and fibronectin 1 after the treatment with pirfenidone, suggesting that although evidence shows its anti-fibrotic effect in proliferative fibroblasts (COLLINS; RAGHU, 2019), the same effect is not perceived in senescent fibroblasts. In agreement with our findings, Roach et al (2021) and collaborators found an increased expression of α-SMA, deposition of collagen 1 and collagen-3, and secretion of soluble collagen after treating fibroblasts with nintedanib and pirfenidone (ROACH; CASTELLS; DIXON; MASON et al ., 2021).…”
Section: Discussionsupporting
confidence: 92%
“…These drugs have been studied in lung fibrosis, where both pulmonary smooth muscle and fibroblasts participate (e.g., Ref. 29 ), and so we also examined their effect on fibroblasts, using the 3T3 fibroblast cell line. Again, FCS-induced growth of 3T3 cells showed a far greater sensitivity to NIN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These observations reveal that IL-1β may reduce local tissue rigidity and provide innate antifibrotic protection that could be important during the early stages of fibrotic processes and lung repair [24]. Other studies have demonstrated that the pan-RTK (receptor tyrosine kinase) inhibitor nintedanib can reduce the mRNA expression for mmp1, 4, 13, and 14 and pirfenidone is able to reduce mRNA expression for mmp3 and 13 [100]. In both cell culture and mouse models of large cell lung carcinoma cell lines (LCC), the overexpression of mmp1 has been described to be necessary for the induction of fibroblast senescence and consequent tumor promotion [101].…”
Section: Mmp-1mentioning
confidence: 85%
“…On the contrary, mmp3-null mice were protected from bleomycin-induced lung fibrosis [29]. Recent studies have described that pirfenidone, a drug approved for IPF treatment reduces mRNA expression of mmp3 in a profibrotic model of human lung fibroblasts stimulated by TGF-β1 [100]. In conclusion, it seems to be clear that MMP-3 has an important profibrotic function in the IPF context.…”
Section: Mmp-3mentioning
confidence: 94%